2023
DOI: 10.31849/utamax.v5i1.9973
|View full text |Cite
|
Sign up to set email alerts
|

English Medium Instruction (EMI) in Higher Education: Insights from Indonesian Vocational Lecturers

Abstract: Reported studies show that some common reasons for offering courses in English medium instruction (EMI) seem to be pragmatic. The rationales for the internationalization of higher education are to improve the English proficiency of both lecturers and students and to facilitate global mobility. However, this responsive practice has some challenges, including limited understanding among university stakeholders of the implications of implementing EMI. This quantitative study examined lecturers' perceptions of EMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…These ideas are related to the idea mentioned by Llagas (2019) that effective communication means expressing ourselves verbally and non-verbally in ways that are appropriate to our cultures and situations. Along with these statements, it can be corroborated with the study of Simbolon (2023), which emphasized the English Medium Instructions (EMI) that in their findings, the lecturers agreed with all three main issues: terms used as a reference to EMI, EMI practice in the classrooms, and necessary support for EMI implementation. Therefore, his study supports the current study's findings that language is a significant consideration when students go abroad because it will affect their ability to communicate better.…”
Section: Discussionmentioning
confidence: 57%
“…These ideas are related to the idea mentioned by Llagas (2019) that effective communication means expressing ourselves verbally and non-verbally in ways that are appropriate to our cultures and situations. Along with these statements, it can be corroborated with the study of Simbolon (2023), which emphasized the English Medium Instructions (EMI) that in their findings, the lecturers agreed with all three main issues: terms used as a reference to EMI, EMI practice in the classrooms, and necessary support for EMI implementation. Therefore, his study supports the current study's findings that language is a significant consideration when students go abroad because it will affect their ability to communicate better.…”
Section: Discussionmentioning
confidence: 57%
“…Overall, this study concluded that the program had produced positive results and that it helped ‘prepare students for international business communication’ (p. 241). Doctoral dissertations on this topic also include Zentz's (2012) ethnographic study of English learners at a Central Java university; and a study by Simbolon (2016), which investigated university teachers’ attitudes to the implementation of EMI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…EMI refers the practice of using English as a medium of instruction in nations where that language is not spoken as a first language (Macaro, 2018). In the Indonesian context, the adoption of EMI is driven by the goals of internationalization and global competitiveness, aiming to facilitate academic mobility (Al Hakim, 2021;(Muttaqin, 2020) Simbolon, 2021;Simbolon, 2023, Sundusiyah, 2023. In this global higher education competition, Indonesian universities strive to be recognized on an international scale (Simbolon, 2021).…”
Section: Introductionmentioning
confidence: 99%